Short-term browsing by roe deer has little effect on survival and growth of sessile oak seedlings. Issue 1 (2nd January 2016) - Bideau, Eric; Maublanc, Marie-Line; Picot, Denis; Hamard, Jean-Pierre; Ballon, Philippe; Gerard, Jean-François
Abstract : We studied the effect of roe deer ( Capreolus capreolus ) browsing on the growth and mortality of sessile oak ( Quercus petraea ) seedlings. First, we measured the height and basal diameter, and counted the number of shoots of the 849 seedlings of an experimental plantation, 60 of which were individually protected by fencing. We then introduced two tame roe deer females every day for three weeks from late May to mid-June. Measurements and counts were repeated after roe deer removal, then once again the following winter. We found no significant effect of browsing on mortality, total height, or basal diameter of the seedlings. However, the browsed seedlings exhibited a lower number of shoots despite regrowth observed after roe deer removal. We propose to use the tolerance of oak to deer browsing to promote natural and inexpensive methods, to protect oak during regeneration, such as the spatial arrangement of plants or the use of slash or surrounding vegetation in favourable environments.